Antimicrobial activity and bioactive profiling of heterocytous cyanobacterial strains using MS/MS-based molecular networking - Saurav, Kumar; Macho, Markéta; Kust, Andreja; Delawská, Kateřina; Hájek, Jan; Hrouzek, Pavel (Folia microbiologica, 2019)
The rapid emergence of resistance in pathogenic bacteria together with a steep decline in economic incentives has rendered a new wave in the drug development by the pharmaceutical industry and researchers. Since cyanobacteria are recognized as wide producers of pharmaceutically important compounds, we investigated thirty-four cyanobacterial extracts prepared by solvents of different polarities for their antimicrobial potential. Almost all tested cyanobacterial strains exhibited some degree of antimicrobial bioactivity, with more general effect on fungal strains compared with bacteria. Surprisingly ~50% of cyanobacterial extracts exhibited specific activity against one or few bacterial indicator strains with Gram-positive bacteria being more affected. Extracts of two most promising strains were subjected to activity-guided fractionation and determination of the minimum inhibitory concentration (MIC) against selected bacterial and fungal isolates. Multiple fractions were responsible for their antimicrobial effect with MIC reaching low-micromolar concentrations and in some of them high level of specificity was recorded. Twenty-six bioactive fractions analyzed on LC-HRMS/MS and Global Natural Product Social Molecular Networking (GNPS) online workflow using dereplication resulted in identification of only forty-nine peptide spectrum matches (PSMs) with eleven unique metabolites spectrum matches (MSMs). Interestingly, only three fractions from Nostoc calcicola Lukešová 3/97 and four fractions from Desmonostoc sp. Cc2 showed the presence of unique MSMs suggesting the presence of unknown antimicrobial metabolites among majority of bioactive fractions from both the strains. Our results highlight potential for isolation and discovery of potential antimicrobial bioactive lead molecules from cyanobacterial extracts.
Keywords: Microbial Sensitivity Tests; tandemová hmotnostní spektrometrie; sinice; grampozitivní bakterie; mikrobiální testy citlivosti; Gram-Positive Bacteria; Cyanobacteria; Tandem Mass Spectrometry; Anti-Bacterial Agents; antibakteriální látky